EMPOWERING HUMAN CAPITAL AND UNEMPLOYMENT IN ECONOMIC GROWTH OF UZBEKISTAN (Conferencea, 2022)
There is a lot of talk about “human capital” today, today the employee is not just an executor, but a strategic resource of the company, the basis of its competitiveness. The main changes in the organization of labor in a modern enterprise are related to the need to take into account not only the priorities of consumers, but also the needs and dignity of employees, both external and internal aspects of activity. The enterprise itself can no longer easily replace one employee with another, as this is the key to the individual capabilities of its components, the competitiveness of the enterprise and its success in the market. It is no coincidence that in recent years a new direction of business services has emerged - "headhunting" associated with the involvement of top managers and highly qualified specialists in the client company. A highly qualified specialist seeks to collaborate with the company, selling to the owners of the company not the ability to work, but the specific results of intellectual activity.